2018
DOI: 10.1002/cti2.1037
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan and arginine catabolic enzymes and regulatory cytokines in clinically isolated syndrome and multiple sclerosis

Abstract: ObjectivesClinically isolated syndrome (CIS) is the earliest clinical episode in multiple sclerosis (MS). A study of circulating cells from patients with CIS may help us understand the transition to, and processes associated with, the development of MS.MethodsAs immune cell activity can be determined by flux through metabolic pathways, the mRNA expression of l‐tryptophan‐ and l‐arginine‐catabolising enzymes, indoleamine 2,3‐dioxygenase (IDO) 1 and IDO2 and arginase (ARG) 1 and ARG2, respectively, was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It is also difficult to hypothesize whether the overexpression of MIF family signatures in CD4 + T cells of CIS patients reflects the preponderance of a particular CD4 T cell subset during CIS and its eventual pathogenetic contribution. In fact, while several studies have well documented the pathogenetic role of upregulated Th1 and Th17 mediated events in the development and progression of MS [29] much less is known on the role of Th subsets and their cytokines in the pathogenesis of CIS although a reduced levels of the anti-inflammatory cytokines IL-10 and TGF-beta has been reported to be associated with the disease [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…It is also difficult to hypothesize whether the overexpression of MIF family signatures in CD4 + T cells of CIS patients reflects the preponderance of a particular CD4 T cell subset during CIS and its eventual pathogenetic contribution. In fact, while several studies have well documented the pathogenetic role of upregulated Th1 and Th17 mediated events in the development and progression of MS [29] much less is known on the role of Th subsets and their cytokines in the pathogenesis of CIS although a reduced levels of the anti-inflammatory cytokines IL-10 and TGF-beta has been reported to be associated with the disease [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen patients with CIS were recruited as part of the PhoCIS trial as previously described, with extensive phenotypic analyses previously performed ( 29 33 ). One additional patient with CIS and eight patients with MS were recruited at diagnosis of a symptomatic demyelinating event, as previously described ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…R848 (Resiquimod) was selected as a polyclonal B cell activator, which mediates its effects via TLR7 and TLR8 [the latter not expressed on B cells ( 36 )]. PBMC were cultured in 96-well U-bottom polypropylene plates at 8 × 10 5 cells per well in RPMI 1640 medium supplemented with 10% FBS, 5 µg/ml gentamicin, 2 mM l -glutamine, 50 µM 2-β-mercaptoethanol (all Sigma-Aldrich) ( 29 ), as well as 1 µL/ml GolgiPlug (BD Biosciences) ( 37 ) in order to maximise detection of intracellular IL-10 and TNF, and to inhibit the effects on B cells of products from activated bystander cells ( 38 ). Where indicated, cell culture medium was supplemented with IgG-IC (100 µg/ml) and/or R848 (500 ng/ml; InvivoGen; San Diego, USA); these concentrations were optimised in preliminary experiments, which also determined that inclusion of GolgiPlug did not substantially alter cell viability (not shown).…”
Section: Methodsmentioning
confidence: 99%
“…For the study, PBMCs were thawed in 10% FBS in RPMI 1640 medium, as previously reported. 14,39 For culture with R848 and intracellular cytokine detection, approximately 8 9 10 5 cells were cultured in RPMI 1640 medium supplemented with 10% FBS, 5 µg mL À1 gentamicin, 2 mm L-glutamine and 50 µm 2-b-mercaptoethanol (all Sigma-Aldrich; Merck, North Ryde, Australia) 12 and 1 µg mL À1 of GolgiPlug (BD Biosciences, North Ryde, Australia) as well as 500 ng mL À1 of R848 (InvivoGen, San Diego, CA, USA) as indicated for 18 h in U-bottom shaped 96-well polypropylene plates at 37°C in 5% CO 2 .…”
Section: Pbmc Collection and Culturementioning
confidence: 99%
“…Many outcomes from the trial have already been published. [11][12][13][14] When the primary outcome of MRI changes was examined, there was a non-significant reduction in the rate of converting from CIS to MS within 12 months in participants who received phototherapy. In the control group of 10, all (100%) had converted while only 7 of the 10 participants who received narrowband UVB had progressed and been diagnosed with MS within 12 months.…”
Section: Introductionmentioning
confidence: 99%